The influence of Islam on Zulu Muslims in KwaZulu-Natal - Ngubane, Simesihle E. (HTS teologiese studies, 2024)
This article explores the influence of Islam among the Zulu Muslims in KwaZulu-Natal (KZN). Although several studies focus on the history and experiences of the Asian diaspora or Asian Muslim community, there is a considerable lack of literature on the influence of Islam on the Zulu Muslims’ personal experiences beyond the conversion narratives. This study seeks to examine the impact of Islam on the cultural and religious identities of individuals who have converted to Islam within the Zulu community. This research article used qualitative research with a phenomenological approach conducted in several areas in KZN. The data for this study were acquired from literature, interviews and observations conducted among the Zulu Muslims in KZN. The data analysis technique employed in this work utilises a comprehensive approach, wherein all the acquired data are considered significant, and no reduction is applied.Contribution: The non-Muslim Zulus in KZN tend to stigmatise Zulu Muslim converts, perceiving them as having abandoned their cultural heritage. The Zulu Muslims who converted to Islam developed their own unique interpretation of the religion by blending Islamic principles with Zulu cultural elements. This allowed them to establish a sense of identity that they believe to be both authentically Zulu and free from colonial influences, in contrast to the Christianised Zulu population.